Effects of tetraalkylammonium salts on alkaline hydrolysis of N-(2-Methoxyphenyl) Phthalimide - Ariffin, Azhar; Khan, M.N.; Leng, S.Y. (Faculty of Science, University of Malaya, 2004)
The effects of the concentrations of Me₄NCI, Pr₄NCl, Bu₄NCl, Me₄NBr, Pr₄NBr and Bu₄NBr on the rate of alkaline hydrolysis of N-(2-methoxyphenyl)phthalimide (N-2MPhPT) at 35°C and in H₂0 solvent containing 2 % (v/v) CH₃CN reveal the formation of ion-pair complexes between solvent - separated loose ion-pair forms ($M^n^+$ ⋯ $X^k^-$) and N-2MPhPT. The bulky hydrophobic tails of tetraalkylammonium salts and their halide anions inhibit the reaction by blocking the OH? nucleophilic attack on the reactive site of N-2MPhPT. Among all the quaternary ammonium salts, Me₄NCI showed slight inhibition only because of the shielding effect created by the methyl group is very small. However, Bu₄NBr presents the greatest inhibition on hydrolysis rate because of its strong binding affmity with N-2MPhPT.